The Integration of Cognitive Remediation Therapy into the Whole Psychosocial Rehabilitation Process: An Evidence-Based and Person-Centered Approach. (2nd July 2012) - Penadés, Rafael; Catalán, Rosa; Pujol, Núria; Masana, Guillem; García-Rizo, Clemente; Bernardo, Miquel
Abstract : Cognitive remediation therapies seem to ameliorate cognitive impairments in patients with schizophrenia. Interestingly, some improvement in daily functioning can also be expected as a result. However, to achieve these results it is necessary that cognitive remediation is carried out in the context of broader psychosocial rehabilitation involving the learning of other communication, social, and self-control skills. Unfortunately, little is known about how to integrate these different rehabilitation tools in broader rehabilitation programs. Based on both the neurocognitive behavioral approach and the action theory framework, a hierarchical flowchart is represented in this paper to integrate CRT with other evidence-based psychological therapies in outpatient settings. Finally, some evidence is provided in which cognitive abilities need to be targeted in remediation programs to improve functioning. In summary, to improve daily functioning, according to these studies, cognitive remediation needs to include the teaching of some cognitive strategies that target executive skills.